Pengaruh POC Kulit Pisang (Musa paradisiaca) Terhadap Pertumbuhan dan Hasil Dua Varietas Selada (Lactuca sativa L.) - Amalia, Nadya Rizky; Wagiono, Wagiono; Subardja, Vera Oktavia (UNIVERSITAS LABUHANBATU, 2023)
The aplication of liquid organic fertilizer is carrid out in an effort to reduce the excessive use of inorganic fertilizers and increase the availability of soil nutriens so that plants can grow and produce optimal production. The purpose of this study was to determine the effect of dose banana peel liquid organic fertilizer (Musa paradisiaca) on the growth and yield of two lettuce varieties (Lactuca sativa L.) on each type of lettuce plants. This research was conducted at Baraya Garden Putra, Youngest Prince Street, Cisarua District, Sumedang Regency, West Java with an altitude of 538 meters below sea level in November 2021 â€“ January 2022. The method used was experimental method with a factorial Randomize Block design (RBD) consisting of two factors with 8 treatments repeated 4 times. The first factor is banana peel liquid organic fertilizer wich consist of 4 levels, namely: P0 (0 ml/L), P1 (70 ml/L), P2 (90 ml/L), and P3 (110 ml/L). The second factor was lettuce varieties consisting of 2 varieties namely: V1 (new grand rapid) and V2 (red rapid). The results of the study showed that there was no interaction effect between the application of banana peel liquid organic fertilizer and the variety on all observation parameters except for the number of leaves aged 35 days after planting. No there was an independent significant effect on the type of variety treatment against all observation parameters except for the leaf area of the plantation. Red rapid variety (V2) gave the highest yield on the height parameter number of leaves, root length, fresh weight, root dry weight, and fresh root weight.Â Keywords: Banana Peel Liquid Organic Fertilizer, New Grand Rapid, Red Rapid